Lelang Eksekusi Kepailitan atas Tanah dan Bangunan yang Dimiliki Bersama oleh Pihak Ketiga dan Debitur Pailit - Putri, Gracia; Fionita, Jessica; Matheus, Juan (Jurnal Supremasi, 2024)
This study examines the execution auction in bankruptcy concerning land and buildings jointly owned by a third party and a bankrupt debtor. The importance of this study lies in protecting the property rights of third parties, which may be at risk during the auction process. There is a research gap in understanding the legal rights of third parties in joint ownership situations with a bankrupt debtor. The objective of this study is to identify the legal implications and protection mechanisms available to third parties. The methodology employed is a normative juridical analysis with a case study approach. The key findings reveal that third parties retain the right to file a lawsuit against the auction as an unlawful act (tort), but their claim of ownership is insufficient to nullify the auction conducted by the Office of State Wealth Service and Auction. This research implies a need for clearer regulations to protect third-party rights in similar cases.